2005
DOI: 10.1038/nn1449
|View full text |Cite
|
Sign up to set email alerts
|

SK channels and NMDA receptors form a Ca2+-mediated feedback loop in dendritic spines

Abstract: Small-conductance Ca(2+)-activated K(+) channels (SK channels) influence the induction of synaptic plasticity at hippocampal CA3-CA1 synapses. We find that in mice, SK channels are localized to dendritic spines, and their activity reduces the amplitude of evoked synaptic potentials in an NMDA receptor (NMDAR)-dependent manner. Using combined two-photon laser scanning microscopy and two-photon laser uncaging of glutamate, we show that SK channels regulate NMDAR-dependent Ca(2+) influx within individual spines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
465
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(496 citation statements)
references
References 43 publications
28
465
3
Order By: Relevance
“…Previous studies have clearly demonstrated that NMDARdependent Ca 2ϩ influx is required for SK channel activation in CA1 neurons (17). Our present data suggest that RyR-mediated Ca 2ϩ release evoked by the Ca 2ϩ influx is important for SK channel activation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have clearly demonstrated that NMDARdependent Ca 2ϩ influx is required for SK channel activation in CA1 neurons (17). Our present data suggest that RyR-mediated Ca 2ϩ release evoked by the Ca 2ϩ influx is important for SK channel activation.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, our observations indicate that the activation of SK channels requires NMDAR-mediated Ca 2ϩ influx in CA1 neurons, as reported in ref. 17. In JP-DKO neurons, APV had no significant effect on action potential configuration, suggesting the disconnection of functional communication between NMDARs and SK channels.…”
Section: Contribution Of Ca 2؉ Release For Sk Channel Activation and Itsmentioning
confidence: 92%
“…SK channels can regulate numerous aspects of neuronal dynamics including: spike frequency adaptation (Pedarzani et al, 2005), dendrosomatic coupling (Cai et al, 2004), as well as synaptic integration and potentiation (Faber et al, 2005;Ngo-Anh et al, 2005). The links between SK channel kinetics and behaviourally relevant neuronal computations have only recently begun to be examined for the SK2 subtype (Ellis et al, 2007b).…”
Section: Sk2 Channels Contribute To Tuning Differences Observed Acrosmentioning
confidence: 99%
“…First, active conductances, including calcium (2), potassium (11), and probably even sodium (12) channels, seem to be located in spines, rendering passive models inadequate to explore the effect of the spine on EPSPs. Second, spines with different morphologies have differences in calcium compartmentalization (13) and in amplitude and kinetics in response to glutamate uncaging (14), raising the suspicion that the spine neck has a major functional role.…”
mentioning
confidence: 99%